PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada SKPD di Kabupaten Kepulauan Anambas ) - Harnoni '; Amries Rusli Tanjung; Edfan darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to test the effect related to human resource capacity, utilization of information technology, and internal control systems of the quality of the financial statements of local government finance in Anambas Island. Data was collected by distributing questionnaires to the respondents. Population in this research is the employee who works on regional work units (SKPD) Anambas Island involved in the preparation of the financial statements, the journal of samples taken at 81 people. The data analysis technique used to test the hypothesis of the research is multiple linear regression analysis using SPSS software version 20.0.These results indicate two variables affect the quality of financial reports and only one variable that does not have an influence on the quality of financial reporting. Two variables that affect the capacity of human resources, internal control system. While the use of information technology has no effect on the quality of local government financial reports.Keyword: Human resource, technology, internal control systems, and financial Statement.